Electronic Beam-Scanning Antenna Based on a Reconfigurable Phase-Modulated Metasurface - Zakaria Zouhdi; Badreddine Ratni; Shah Nawaz Burokur (Sensors, 2022)
Metasurfaces (MSs) have enabled the emergence of new ideas and solutions in the design of antennas and for the control of electromagnetic waves. In this work, we propose to design a directional high-gain reconfigurable planar antenna based on a phase-modulated metasurface. Reconfigurability is achieved by integrating varactor diodes into the elementary meta-atoms composing the metasurface. As a proof of concept, a metasurface prototype that operates around 5 GHz is designed and fabricated to be tested in an antenna configuration. The metasurface is flexibly controlled by different bias voltages applied to the varactor diodes, thus allowing the user to control its phase characteristics. By assigning judiciously calculated phase profiles to the metasurface illuminated by a feeding primary source, different scenarios of far-field patterns can be considered. Different phase profiles are tested, allowing us to, firstly, achieve a highly directive boresight radiation and, secondly, to steer the main radiated beam towards an off-normal direction. The whole design process is verified by numerical simulations and is validated experimentally by far-field antenna measurements. The proposed metasurface enables the design of directive flat antennas with beam-scanning characteristics without complex feeding systems and power-consuming phase shifters, and thus provides potential interests for next generation antenna hardware.